Keefektifan Pembelajaran Keterampilan Bertanya dengan Metode Question Student Have Siswa Kelas VII SMP Negeri 1 Sinjai - Ilham Bachtiar; Busyairi Ahmad (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2019)
The objective of this research was to prove the learning effectiveness of seventh grade students’ questioning skill using “Question Student Have” method in SMP Negeri 1 Sinjai. The instrument for the research was observation which using checklist form about students’ participation in questioning in Indonesian learning. In analyzing the data, the researcher used descriptive analysis and inferential analysis. The result showed that the “Question Student Have” method was effective to be implemented in Indonesian teaching and learning. This is proven by the result of data observation in which the students’ (in experiment class) participation and enthusiastic in questioning is bigger than the students who were in control class. It is indicated by the average score of the students’ in experiment class were higher than the students’ average score in control class which the scores were 5,75 (experiment class) and 3, 38 (control class). Besides, the statistic showed that t count > t table = 4,90 > 2,00 and the significance was 5% which means the hypothesis was accepted.